2022
DOI: 10.14309/ajg.0000000000001680
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Barrett's Esophagus: An Updated ACG Guideline

Abstract: Barrett's esophagus (BE) is a common condition associated with chronic gastroesophageal reflux disease. BE is the only known precursor to esophageal adenocarcinoma, a highly lethal cancer with an increasing incidence over the last 5 decades. These revised guidelines implement Grading of Recommendations, Assessment, Development, and Evaluation methodology to propose recommendations for the definition and diagnosis of BE, screening for BE and esophageal adenocarcinoma, surveillance of patients with known BE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
294
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(310 citation statements)
references
References 239 publications
5
294
0
11
Order By: Relevance
“…It is well known that LGD is a challenging diagnosis and guidelines therefore recommend expert pathologist review for each LGD diagnosis 8 9 10 11 . The differentiation between reactive inflammatory changes and early dysplasia is complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that LGD is a challenging diagnosis and guidelines therefore recommend expert pathologist review for each LGD diagnosis 8 9 10 11 . The differentiation between reactive inflammatory changes and early dysplasia is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a subtle lesion may also have been missed during the second endoscopy, with additional delay and risk for progression. The Dutch and European BE guidelines recommend that patients with confirmed LGD are referred to an expert center for re-staging within 3 months, whereas US guidelines advise re-staging after 3–6 months with high definition and (optical) chromoendoscopy, not necessarily at an expert center 8 9 10 28 29 . Considering the high rates of worse histopathology found at the expert endoscopy, we would advocate for re-staging within 3–6 months upon referral in an expert center as advised by the Dutch and European guideline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this hypothesis should be confirmed by further study that includes more endoscopists. Nevertheless, a gastroenterology training curriculum should provide training in IEE for premalignant and early gastric cancer detection instead of implementing random biopsy for surveillance of many early gastrointestinal malignancies, such as GIM 5 21 and Barrett’s esophagus (BE) 22 23 . For instance, in 2016, a guideline from the American College of Gastroenterology (ACG) strongly suggested that at least eight biopsies be taken in patients with BE during EGD surveillance 22 .…”
Section: Discussionmentioning
confidence: 99%